1981
DOI: 10.1007/bf01353062
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of specific conversational behaviors to ratings of social skill: An experimental analysis

Abstract: Research on the social effectiveness of specific conversational behaviors is reviewed and a new study is presented. Eight versions of theWe would like to thank the following people who helped with the study: Marianne Morino, who helped write the scripts; Colleen Kelley and David KeUiher, who were the actors; Debbie Mahoe and Rebecca Gaslin, who were experimenters; and John Wright, who helped with the data reduction. We would also like to thank radio station KWAX for allowing us to use their facilities. A previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…A clear limitation of these studies is their use of ratings of videotaped or written descriptions of behavior. Parallels between results of rating studies and those of direct observation studies have been found in research on other social behaviors (e.g., Dow, Glaser, & Biglan, 1981). Consistencies between these results and direct observation studies of reactions to distressed (Biglan et al, 1985;Hops et al, 1987) and aggressive behavior (Patterson, Reid, & Dishion, in press) are encouraging.…”
Section: Discussionsupporting
confidence: 56%
“…A clear limitation of these studies is their use of ratings of videotaped or written descriptions of behavior. Parallels between results of rating studies and those of direct observation studies have been found in research on other social behaviors (e.g., Dow, Glaser, & Biglan, 1981). Consistencies between these results and direct observation studies of reactions to distressed (Biglan et al, 1985;Hops et al, 1987) and aggressive behavior (Patterson, Reid, & Dishion, in press) are encouraging.…”
Section: Discussionsupporting
confidence: 56%
“…Based on previous conversational skills research (Kelly et a/., 1980;Minkin et a/., 1976;Dow et al, 1981), 3 conversational skill components were selected for training as a function of their fundamental contribution toward conversational competence.…”
Section: Targeted Conversational Skill Componentsmentioning
confidence: 99%
“…Furthermore, few investigators have used an empirical validation approach in selecting target behaviors. The relevance of specific conversational components to evaluators’ ratings of social skill has been socially validated in several investigations (Minikin et al 1976; Romano and Bellack 1980; Dow et al 1981). However, most researchers have chosen the specific components for training based on face validity alone, and have arbitrarily judged treatment outcome without reference to criterion levels that may be appropriate in a particular interpersonal context.…”
Section: Behavioral Model Of Social Skills and Schizophreniamentioning
confidence: 99%